Factors influencing regional disparities in online shopping - M. Olumekor (Цифровая социология)
Online shopping has grown exponentially in the Russian Federation (hereinafter referred to as RF, Russia) in recent years. This growth has significantly accelerated during the COVID-19 pandemic. However, data shows that there are inter-regional disparities in the use of online shopping. This includes intergenerational and rural-urban disparities. This study investigates the factors responsible for inter-regional differences in the development of online shopping in Russia. The author has identified 5 main factors that can influence the development: internet infrastructure (measured by regional expenses for the introduction of digital technologies and the number of connected mobile subscribers), economic wealth (measured by gross regional product), standard of living (measured by the population income), rate of poverty, and the region’s population. The research uses data of the Federal State Statistics Service and Association of Internet Trade Companies to analyse 85 regions in the RF. A multi-level regression analysis has enabled examination of the 5 factors and the contextual influence of 8 federal districts of Russia in level 2. The results show that internet infrastructure, economic wealth, population size, and the 8 federal districts has influenced the development of online shopping in the RF, but standard of living is not statistically significant. The author recommends that policymakers pay attention to these underlying factors.